If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -3x = 6x + 7 Reorder the terms: 16 + -3x = 7 + 6x Solving 16 + -3x = 7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 16 + -3x + -6x = 7 + 6x + -6x Combine like terms: -3x + -6x = -9x 16 + -9x = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 16 + -9x = 7 + 0 16 + -9x = 7 Add '-16' to each side of the equation. 16 + -16 + -9x = 7 + -16 Combine like terms: 16 + -16 = 0 0 + -9x = 7 + -16 -9x = 7 + -16 Combine like terms: 7 + -16 = -9 -9x = -9 Divide each side by '-9'. x = 1 Simplifying x = 1
| 48k=-276 | | 6x(2)+1-n+5n(2)= | | 6519.88-150.99w=3500 | | 3z+8=13+3x-z | | -2a-9=6a+5 | | 3500-150.99w=-6519.88 | | 2+2x+7=-6 | | 20+14=28+13 | | -49+3k=k-5k | | findy-7x+7y=105 | | 3500+150.99w=6519.88 | | 14-11x=3x^2 | | 3500-150.99w=6519.88 | | (4x+8)=4x-12 | | 5x+6=2x+4 | | 7x^2+62x+48=0 | | 14-1x=3x^2 | | -33+4p=-1+4(p-8) | | -16x+72=20-12x | | 23-5h= | | 32x+40=y(4x+5) | | (3x-1)=-9 | | 12(2k+11)=-12(2k+12) | | 7(2x+5)=4(x+2)-20x | | 6x^2+6y^2+12x=24 | | -17m-15=70 | | -17x^2-17x+5=0 | | k+9/4=k+7/8 | | Y+4c=10x-6 | | 4x-4=2(x+6) | | 18x^2+12x-16=0 | | k+9/=k+7/8 |